KEMAMPUAN LITERASI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL DITINJAU DARI GAYA BELAJAR DAVID KOLB - Elisa Amelia; Heni Pujiastuti; Hepsi Nindiasari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Researchers in this article describe the mathematical literacy skills of junior high school students in solving social arithmetic problems in terms of David Kolb's learning style. This research method uses descriptive qualitative with 26 students of SMPN 2 Cileles class VIII B as the research subjects. This study used mathematical literacy test instruments, David Kolb learning style questionnaire, and interview guidelines. The results showed that each learning style had varied mathematical literacy skills.  Upper divergent students were able to fulfill three mathematical process indicators. Middle divergent students are only able to formulate the context mathematically and use mathematical concepts, facts and procedures. Lower divergent students are only able to formulate the context mathematically. Upper assimilation students were able to fulfill three process indicators Moderate assimilation students were able to fulfill three process indicators in part of the problem. Lower assimilation students were only able to formulate the context mathematically. Upper and medium convergent students were able to fulfill the three mathematical process indicators in part of the problem. Lower convergent students are only able to formulate the context mathematically. Upper and medium accommodation students were able to fulfill three mathematical process indicators in part of the problem. Lower accommodation students were only able to fulfill one process indicator, namely formulating the context mathematically